WEBSITE KELURAHAN SOLOK SIPIN - simorangkir, lucy; Sukmana, Anugerah (LP2M Universitas Nurdin Hamzah, 2024)
The smallest government agency at village level is the sub-district office, which is an agency that handles population data processing, especially in the process of making family cards, birth certificates, death certificates, immigrant certificates and moving certificates. In terms of data processing, Kelurahan Solok Sipin still experiences several obstacles, resulting in a long time in making reports. To overcome this, a web-based application is needed to speed up or simplify work and data and provide information more quickly and accurately. This application aims to make it easier for sub-district officials to improve population data collection and reports. The input requirements are admin data, population data, family card data, transfer mutation data, migrant mutation data, and birth event data. For process requirements, namely population data processing, family card data processing, transfer and immigrant mutation data processing, and processing data on birth and death events. The output requirements are population data reports, family card data reports, migration transfer data reports, migrant mutation data reports, and birth event data reports. So the expected results in this research are wide accessibility, no installation required, and updates can be automatic.